Implementasi manajemen risiko dalam pembiayaan mudharabah pada bank syariah di indonesia: Analisis komprehensif dan model mitigasi adaptif - Choirunnisa, Prima Ananda (Maliki Interdisciplinary Journal, 2025)
Mudharabah financing as the flagship product of Islamic banking based on profit-sharing principles faces unique and challenging risk management complexities. This research analyzes specific risk characteristics in mudharabah financing, evaluates risk management frameworks applied by Indonesian Islamic banks, and develops adaptive risk mitigation models. Using a qualitative approach with comprehensive descriptive analysis of Islamic banking risk management practices, this study identifies three main risks: asymmetric information, moral hazard, and adverse selection. Findings indicate that existing risk management frameworks are not optimal in accommodating the unique characteristics of mudharabah contracts. Based on bibliometric mapping and current literature review, the research recommends developing technology-based screening systems, improving real-time monitoring, and regulatory adaptation responsive to profit-sharing-based financing dynamics.